Classroom management: Applying appropriate strategies to enhance effective teaching - Purwanti, Eko; Vania, Gitta (Universitas Muhammadiyah Yogyakarta, 2021)
The teaching and learning process should be conducted effectively so that students can obtain the learning objectives. In so doing, teachers should have the ability to deliver the teaching materials effectively by conducting good classroom management. In this case, as prospective teachers, pre-service teachers should manage the classroom well to maintain teaching effectively. However, handling classroom management is not easy, and therefore pre-service teachers should apply appropriate strategies in managing the classroom. This research aims to investigate the strategies that pre-service teachers use to overcome the problems in managing the classroom during their teaching practices in a private senior high school. A qualitative research approach was employed to answer the research questions, in which in-depth interviews were administered to collect the data. Besides, four pre-service teachers at an Islamic university in Yogyakarta volunteered as the participants in this study. This study’s results showed that the participants applied several strategies to respond to the problems emerging during their teaching practice. The strategies which these pre-service teachers applied to overcome the problems comprised 1) improving self-confidence, 2) preparing lessons carefully, 3) anticipating unpredictable situations, 4) responding to unpredictable questions wisely, and 5) handling with the students’ heterogeneity. Having various ways of handling classroom management, these pre-service teachers could deliver the lesson effectively. Therefore, this study is beneficial for those who are having teaching practice to keep the classroom run successfully.